Novel precursors for anatase nanorods and their application in DSSCs - Mishra, Biswajit; Agarkar, Shruti A.; Khushalani, Deepa (Materials Chemistry and Physics, 2014)
Syntheses for the formation of two new precursors for TiO2 nanorods: titanium propanediolate and titanium erythritolate, have been detailed. These precursors have a rod like morphology and have been found to have higher thermal stability than commercially available precursors. The conversion of the precursors to anatase phase of TiO2 involves a simple heating protocol and importantly the morphology is conserved. The resulting anatase nanorods have been characterised and evaluated as photoanodes in dye sensitized solar cells (DSSCs). Overall device efficiencies of 3.2% and 2.3% were achieved when anatase rods (obtained from titanium propanediolate and titanium erythritolate respectively) were used. These values are higher than the 1.1% efficiency obtained from the control device (made with spherical anatase nanoparticles). It is found that forming ordered 1-D rods leads to enhanced charge transport and charge collection at the electrode along with a commensurate decrease in charge recombination. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Inorganic compounds; Nanostructures; Non-crystalline materials; Sol-gel growth

Synthetic precursor to vertical TiO2 nanowires - Mishra, Biswajit; Ghildiyal, P.; Agarkar, Shruti A.; Khushalani, Deepa (Materials Research Express, 2014)
An easy protocol for improvement in formation of the photoanode in a dye sensitized solar cell is addressed. Specifically, a novel synthesis for the formation of a TiO2 precursor: titanium butanediolate, is detailed. This precursor is found to have higher thermal and temporal stability than commercially available TiO2 precursors and it has successfully been employed in the one-pot synthesis of rutile nanowires grown directly on a conducting substrate: fluorine doped tin oxide (FTO). This synthesis has been further extended to directly form a mixed phase TiO2 film consisting of rutile nanowires along with anatase spherical particles on FTO and this assembly has been used as the photoanode in a dye-sensitized solar cell. The synergistic effect of the two phases has provided a net DSSC efficiency of 4.61% with FF = 61%.
Keywords: Nanomaterials; Nanowires; TiO2

Enhancement in rate of photocatalysis upon catalyst recycling - Sorathiya, Kalpesh; Mishra, Biswajit; Kalarikkal, Abhishek; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Khushalani, Deepa (Scientific Reports, 2016)
Recyclability is an important aspect for heterogeneous photo-catalysts. Ease of recovery and stability of the photo-catalyst in terms of efficiency over the number of cycles are highly desired and in fact it is ideal if the efficiency is constant and it should not decrease marginally with each cycle. Presented here is a seminal observation in which the photocatalytic activity is shown to improve with increasing number of catalytic cycles (it is 1.7 times better after the 1st cycle and 3.1 times better after the 2nd cycle). Specifically, nanorods of pure TiO2 and TiO2 doped with controlled amount of tungsten have been used to degrade two model pollutants: Phenol and Rhodamine B under exclusive visible light illumination. It was found that, in case of 1 mol.% W incorporation, rate of photocatalysis and also the range of visible light absorption of the photocatalyst increased after the photocatalysis as compared to before photocatalysis. This aspect is unique for doped TiO2 and hence provides an intriguing way to mitigate low photoactivity.